From Prescription to Plate: Evaluating Drug-Drug and Drug-Food Interactions in the Prescriptions Dispensed in Community Pharmacies of Northern Cyprus - Karatasli, Ozgur; Shah, Syed Sikandar; Alam, Aftab; Rabbani, Syed Arman; Tamirci, Mevhibe (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: The effect of drug on a person may be different than anticipated when the drug interacts with another drug/drugs the person is taking, or the food, beverages and dietary supplements the person is consuming. Materials and Methods: A total of 750 prescriptions were obtained from four different pharmacies of the Turkish Republic of Northern Cyprus. These prescriptions were evaluated for the drug-drug interactions, drug-food interactions and the legibility of the prescription format and the availability of the information about the prescribed drugs. The prescriptions were examined regarding the availability of the information about the patient and physician name/surname, the age of the patient, the date of the prescription, the specialty of the physician and the name of the hospital/clinic. It was determined that 87.6% of the prescriptions did not include diagnostic information. Results: A total of 1461 drugs were written in 750 prescriptions, and the average number of drugs per prescription was 1.95±1.02. In total, 132 drug-drug interactions were observed in prescriptions. On classification of severity of these interactions, 10.6% were found to be major, 71.21% were moderate and 18.18% of them were minor. The most frequent Drug-Drug Interactions (DDIs) were detected between paracetamol-hyoscyamine (n=5) and ciprofloxacin-ketoprofen (n=4). The most common DDIs were between musculo-skeletal system drugs (42.9%), followed by DDIs between anti-infectives for systemic use (28.6%) and other drugs, and cardiovascular system drugs (21.4%). The most frequent drug-food interactions were between ciprofloxacin (n=22), chlorpheniramine (n=21) and metronidazole (n=18) with food. According to these, it was observed that the most common drug-food interactions was between anti-infective for systemic use, respiratory system drugs and antiparasitic products, insecticides and repellents. Conclusion: Drug-drug interactions and drug-food interactions are frequently overlooked and undervalued. Such interactions can have a significant role in the development of adverse drug reactions. Polypharmacy is one of the leading causes of DDIs, a comprehensive examination of the patient’s health and medications should be performed prior to prescribing or adding additional prescriptions to their present treatment regimen.
Keywords: Drug-food interactions; Drug-drug interactions; Polypharmacy; Prescriptions